(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Abstract A shelter house is a place that provides additional protection and education for street children according to individual needs at the location of the halfway house. The presence of halfway houses is very important because there is an increasing inequality in development, the demands of modern life, and the amount of information that makes competition in the real world even more fierce. Public Market Pinasungkulan Karombasan Manado there are many street children (about 65 people) aged between 9 to 16-17 years who are active in a shelter called "Sanggar Kasih Asih-Asah-Asuh" This shelter has not been managed properly, there are many shortcomings, especially in teaching methods, time, availability of course materials, and sometimes even a lack of sufficient food. An effort is underway to help Sanggar Kasih survive for two years by providing an integrated learning program as well as regular nutrition support enhancements. With the empowerment carried out over the past year, there has been a significant change in the management of the Asih-asah-asuh shelter where the children have joy and additional knowledge, an integrated way of learning and most importantly their free time is filled with programmed knowledge learning, learn ethics and religion, and having good nutrition additions.